2000
DOI: 10.1073/pnas.050002197
|View full text |Cite
|
Sign up to set email alerts
|

Defensive use of a fecal thatch by a beetle larva ( Hemisphaerota cyanea )

Abstract: The larva of the tortoise beetle, Hemisphaerota cyanea (Chrysomelidae, Cassidinae), constructs a thatch from long filamentous fecal strands, beneath which it is totally concealed. The thatch is not discarded at molting but is enlarged by addition of strands as the larva grows. Thatch construction begins when the larva hatches from the egg. Pupation occurs beneath the thatch. Two predators, a coccinellid beetle larva (Cycloneda sanguinea) and a pentatomid bug (Stiretrus anchorago), were shown to be thwarted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 15 publications
2
40
0
Order By: Relevance
“…Several authors have shown that the protection is provided by chemical compounds found in the fecal shield (Gómez et al, 1999;. Although Root & Messina (1983) and Eisner & Eisner (2000) have suggested that fecal shields provide physical protection to larvae, and have shown that this kind of protection does not occur in the chrysomelids Lema trilinea, Neolema sexpunctata, and Blepharida rhois.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have shown that the protection is provided by chemical compounds found in the fecal shield (Gómez et al, 1999;. Although Root & Messina (1983) and Eisner & Eisner (2000) have suggested that fecal shields provide physical protection to larvae, and have shown that this kind of protection does not occur in the chrysomelids Lema trilinea, Neolema sexpunctata, and Blepharida rhois.…”
Section: Introductionmentioning
confidence: 99%
“…Females can put feces on their eggs, providing an efficient chemical repellent and physical barrier against parasitoids and predators (Damman & Cappuccino, 1991;Hilker, 1992;Olmstead, 1994). Larvae can carry masses of exuviae and feces that accumulate on a fork-like structure located on the last segment of the abdomen, forming a shield-like structure (Eisner & Eisner, 2000). Previous studies have demonstrated that the shield provides protection against various groups of predators (Eisner et al, 1967;Root & Messina, 1983;Olmstead & Denno, 1993;Vencl et al, 1999;Eisner & Eisner, 2000), but there are also cases in which fecal shields can serve as an attractive cue for generalist predators (Müller & Hilker, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shields of species lacking fecula (feces), and presumably chemical components therein, function as simple physical barriers that thwart attacking enemies (Root and Messina 1983;Eisner and Eisner 2000). Tortoise beetles that vigorously wave their shields can beat back attacking predators (Eisner et al 1967;Go´mez 1997;Chaboo 2002;Mu¨ller 2002;Nogueira-de-Sa´and Trigo 2002); however, shields appear to be more than simple barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Some species use shields, which vary in appearance www.witpress. com, ISSN 1743-3541 (on-line) and physical consistency, in order to deter a number of predators [26]. Other organisms employ complex noxious substances or venom as a predator deterrent strategy [27].…”
Section: An Analogy Between Crime and Biological Situationsmentioning
confidence: 99%